2005
DOI: 10.1002/ajpa.20293
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of hot flash frequencies: Considering climatic influences

Abstract: Laboratory studies suggest that hot flashes are triggered by small elevations in core body temperature acting within a reduced thermoneutral zone, i.e., the temperature range in which a woman neither shivers nor sweats. In the present study, it was hypothesized that women in different populations develop climate-specific thermoneutral zones, and ultimately, population-specific frequencies of hot flashes at menopause. Correlations were predicted between hot flash frequencies and latitude, elevation, and annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Women in warmer temperatures report fewer hot flushes, and the difference between the hottest and coldest temperatures was also a significant predictor. 64 Conversely, others have reported a direct relation between warmer climate and more intense hot flushes. 23 A direct relation between hot flushes and the number of cigarettes smoked has been 65 This was not the case in our series, perhaps because of the fact that smoking habit is low among middleaged Latin American women.…”
Section: Discussionmentioning
confidence: 96%
“…Women in warmer temperatures report fewer hot flushes, and the difference between the hottest and coldest temperatures was also a significant predictor. 64 Conversely, others have reported a direct relation between warmer climate and more intense hot flushes. 23 A direct relation between hot flushes and the number of cigarettes smoked has been 65 This was not the case in our series, perhaps because of the fact that smoking habit is low among middleaged Latin American women.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, the analysis indicated that hot flush frequency appears to increase as the difference in temperatures between the hottest and coldest months increase. In other words, women living in seasonal climates may have greater sensitivity to temperature changes and this may explain, in part, why there is variation in hot flush frequency in different areas of the world 76 . The authors speculated that women in warmer climates report fewer hot flushes because they may have a reduced sensitivity to elevated temperatures or because they attribute warming sensations to the ambient warmth rather than hot flushes.…”
Section: Climatementioning
confidence: 99%
“…Factors associated with somatic, emotional, and vasomotor symptom experience at midlife include menopausal status (Avis et al 2001;Kuh et al 1997;Guthrie et al 2004;Melby et al 2011), smoking, socioeconomic status (Avis et al 1997), education (Schwingl et al 1994;Brambilla et al 1989), culture/cultural significance (Beyene 1989;Lock 1998;Robinson 1996;Melby et al 2005), diet (Nagata et al 2000) and environment/climate and seasonality (Sievert and Flanagan 2005). Studies of midlife have also suggested that psycho-social stress is a significant correlate of symptom frequencies in Canada (Kaufert et al 1992), the UK (Kuh et al 1997), the U.S. (McKinlay et al 1987;Thurston et al 2008), Spain (Sievert et al 2007b), Japan (Igarashi et al 2000), and Chile (Binfa et al 2004).…”
Section: Introductionmentioning
confidence: 99%